2012
DOI: 10.1016/j.juro.2012.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy: AUA Guideline

Abstract: Vasectomy should be considered for permanent contraception much more frequently than is the current practice in the U.S. and many other nations. The full text of this guideline is available to the public at http://www.auanet.org/content/media/vasectomy.pdf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
262
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(274 citation statements)
references
References 44 publications
7
262
2
3
Order By: Relevance
“…Furthermore, concerns have been raised about bias, unmeasured confounding, and chance in relation to the small increased risk found by others 2554 Recently published meta-analyses of these studies found that vasectomy was not associated with risk of prostate cancer,6 7 and guidelines from the American Urological Association in 2012 recommended that clinicians do not need to routinely discuss prostate cancer during preoperative counselling of men considering vasectomy 55…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concerns have been raised about bias, unmeasured confounding, and chance in relation to the small increased risk found by others 2554 Recently published meta-analyses of these studies found that vasectomy was not associated with risk of prostate cancer,6 7 and guidelines from the American Urological Association in 2012 recommended that clinicians do not need to routinely discuss prostate cancer during preoperative counselling of men considering vasectomy 55…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the American Urological Association (AUA) guidelines were amended to include 100,000 nonmotile sperm per mL in an uncentrifuged specimen as a measure of postvasectomy success. 7 These guidelines have reportedly improved patient compliance and have decreased repeat vasectomies, the number of semen analyses, and the time and use of alternate contraception while awaiting sterility results. 8 Despite equal access to health care in the military system, service members are frequently relocated and often deployed to austere combat environments, hampering follow-up.…”
mentioning
confidence: 99%
“…One meta-analysis reported an elevated risk of prostate cancer after vasectomy (RR 1.37, 95%CI 1.15-1.62), with a linear trend suggesting a 10% increase for each additional 10 years since vasectomy up to 30 years (RR 1.32, 95%CI 1.17-1.50) (17). Nevertheless, the results of two other meta-analyses showed no difference in the risk of prostate cancer between subjects with and without a history of vasectomy, regardless of the time since surgery (18,19). Our study demonstrated an inverse relation between vasectomy and prostate cancer (non-adjusted RR 0.26, 95%CI 0.06-1.04, p < 0.05).…”
Section: Discussionmentioning
confidence: 98%